Weed Control in Sweet Potato - William M. Stall (EDIS, 2010)
Revised! HS198, a 3-page fact sheet by William M. Stall, provides updated recommendations for weed control in sweet potato. Published by the UF Department of Horticultural Sciences, March 2010.